Effectiveness of ginger and cinnamon compresses on pain in elderly with osteoarthritis - Fitriani, Nur; Supriyadi, Supriyadi (Proceedings Series on Health & Medical Sciences, 2020)
Osteoarthritis (OA) was one of the most common chronic diseases and a major cause of pain and disability that decreased health status. This disease caused pain and disability in patients which disturbed daily activities. Warm compress is one of the non-pharmacological therapies used to reduce pain. Warm compress therapy is applied at the sub-acute and chronic stage of osteoarthritis to reduce pain, compression and pain in the joints. Warm compresses can be combined by adding ginger and cinnamon. The aim of the reaesarh to understand the effectiveness of ginger and cinnamon compresses on lowering pain in the elderly with osteoarthritis in the orphanage of Sudagaran. This research was quasi-experimental design with two pretest-posttest design groups was used in this study. The samples were collected by using a random sampling technique with a total of 15 respondents getting ginger compress and 15 respondents getting cinnamon compress which was in accordance with the inclusion and exclusion criteria. The data were analyzed by using univariate and bivariate with Mann Whitney U Test. The results of the Mann Withney U Test on the second post-therapy obtained the difference in the value of ginger compresses with p = 0.417 and the difference in comfort value of cinnamon compresses with p = 0.127. After calculating the size effect, the ginger size effect was 0.924 while the cinnamon size effect was 0.790. The use of ginger compresses is more effective than cinnamon compresses in lowering pain in the elderly with osteoarthritis in the Community Health Center of Sudagaran.